2018
DOI: 10.1111/jora.12456
|View full text |Cite
|
Sign up to set email alerts
|

Person‐Environment Fit and Positive Youth Development in the Context of High School Gay–Straight Alliances

Abstract: Drawing from a person-environment fit framework, we identified profiles of youth in gay-straight alliances (GSAs) based on the extent to which they received information/resources, socializing/support, and advocacy opportunities in their GSAs and the extent to which this matched what they desired from their GSA along these three functions. Further, we examined profile differences in positive developmental competencies while accounting for community-contextual factors. In a sample of 290 youth from 42 Massachuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…Although GSAs share a common trait—their focus on LGBTQ student topics—beyond this, they may vary widely in their structure, activities, and goals (Griffin et al, 2004), and students may vary regarding what they want from their GSA (Calzo et al, 2020). Prior studies have indicated that certain club qualities and activities may strengthen the potential benefits of GSA attendance (Ioverno & Russell, 2020; Lapointe & Crooks, 2018; Poteat et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Although GSAs share a common trait—their focus on LGBTQ student topics—beyond this, they may vary widely in their structure, activities, and goals (Griffin et al, 2004), and students may vary regarding what they want from their GSA (Calzo et al, 2020). Prior studies have indicated that certain club qualities and activities may strengthen the potential benefits of GSA attendance (Ioverno & Russell, 2020; Lapointe & Crooks, 2018; Poteat et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Many schools, for example, have Gay-Straight Alliances (GSAs; also known as Gender and Sexuality Alliances). These student-led school-based organizations provide a safe environment for LGBTQ and heterosexual youth to receive support, socialize with peers, access LGBT-specific information and resources, and engage in advacacy efforts (Calzo, et al, 2018;Poteat et al, 2012;Russell, Muraco, Subramaniam, & Laub, 2009). A growing body of literature supports that the presence of GSAs is associated with lower rates of truancy, substance use and suicidal behavior (Poteat et al, 2012), fewer incidence of harassment and victimization and greater feelings of safety among LGBT and heterosexual students (Ioverno et al, 2016;Marx & Kettrey, 2016).…”
Section: Adolescent Sexual Identity and Social Changementioning
confidence: 99%
“…It is therefore vital that schools do not only focus on creating a safe and inclusive school climate, but also provide clear information to adolescents about how they can access supportive and potentially anonymous resources that can help them when they experience victimization. Furthermore, to decrease victimization disparities and improve SGM adolescents' well-being, schools can use Lesbian, Gay, Bisexual, Transgender, and Questioninginclusive sex education [32] or more specific student-directed initiatives, known as Gender Sexuality Alliances [33,34]. Finally, it is vital that inclusion and diversity are mandatory topics in school staff's training curriculum.…”
Section: Discussionmentioning
confidence: 99%